THE AGRICULTURAL SECTOR OF UKRAINE AS A COMPONENT OF FOOD SECURITY UNDER THE MARTIAL LAW - Valentyna Ilina; Anna Ilina (Environmental Problems)
The problems of monitoring and assessing the state of the agricultural sector as an integral part of food security of the country are considered. Along with other countries, Ukraine is one of the world’s leading food security countries. Grain production is one of the leading industries in the agricultural sector. Ukraine is one of the largest exporters of grain and pulses in the world. The structure of sown areas in Ukraine by types of crops is analyzed, and the main problems in connection with active hostilities in certain regions are identified. The key problems of reducing the total gross harvest, the disruption of supply chains and, as a result, the increase in the food prices around the world have been identified. Due to the growing global food crisis around the world, ensuring food security has become a primary and priority task. The article analyzes the indicators used to assess food security. The need to make adjustments to the approaches to optimizing the grain crops areas in Ukraine in the conditions of military operations and their consequences in the future was substantiated. To minimize the consequences, it is necessary to protect and support the agricultural production in Ukraine under the martial law as soon as possible. There is a list of the main measures that will help improve food security under military occupation.